A Progress Report and Roadmap for Microphysiological Systems and Organ-On-A-Chip Technologies to Be More Predictive Models in Human (Knee) Osteoarthritis - Rothbauer, Mario; Reihs, Eva I.; Fischer, Anita; Windhager, Reinhard; Jenner, Florien; Toegel, Stefan (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoarthritis (OA), a chronic debilitating joint disease affecting hundreds of million people globally, is associated with significant pain and socioeconomic costs. Current treatment modalities are palliative and not able to stop the progressive degeneration of articular cartilage in OA. Scientific attention has shifted from the historical view of OA as a wear-and-tear cartilage disorder to its recognition as a whole-joint disease, highlighting the contribution of other knee joint tissues in OA pathogenesis. Despite much progress in the field of microfluidic systems/organs-on-a-chip in other research fields, current in vitro models in use do not yet accurately reflect the complexity of the OA pathophenotype. In this mini review, we provide (1) a detailed overview of the most significant recent developments in the field microsystem approaches for OA modeling, as well as (2) an OA-pathophysiology-based bioengineering roadmap for the requirements of the next generation of more predictive and authentic microscale systems fit for the purpose of not only disease modeling but also of drug screening to potentially allow OA animal model reduction and replacement in the near future.